Implementation of Drug (Narcotics) Convicts Development Models in The Correctional Institution - Supanto Supanto; Ismunarno Ismunarno; Sabar Slamet; Tika Andarasni Parwitasari; Rofikah Rofikah (Jurnal Dinamika Hukum, 2020)
This research aims to examine the answers to problems related to the studyof the differences in the development of the drug convicts as regulated in LawNumber 12 of 1995 concerning Corrections. Accompanied by the implementationof guidance carried out by correctional officers for the drug (narcotics) assistedresidents, especially drug users so that these assisted residents can be re-socialized in order to realize restorative justice and the public can accept their presence again. There are several obstacles to coaching drug convicts, especially narcotics users. This study uses primary and secondary data. Direct interviews obtained primary data because during the Covid 19 pandemic; interviews were conducted online with the Cipinang Penitentiary's narcotics. Secondary data is taken from books, magazines, journals on the development of narcotics convicts. After the data has been collected, data processing and analysis are carried out and presented in the form of a report resulting from the research. From the research, it is concluded that there are differences in the coaching of the Narcotics criminal offenders concerning the intentions, the health conditions of the perpetrators and some of the coaching carried out in Correctional Institutions, especially medical, social, psychological rehabilitation, several things become obstacles in coaching, including the problem of apparatuses coordination, differences the understanding of the judge tends to punish, not rehabilitation, neglect of assessment. Keywords: Model, Development, Convict, Narcotics.